THE WORK OF A PSYCHOLOGIST ON THE FORMATION OF WOMEN’S PSYCHOLOGICAL READINESS FOR MATERNITY (Psychology Travelogs, 2023)
The article is devoted to the currently extremely important problem of psychological readiness for motherhood. The paper offers an overview of research on the level and features of the formation of psychological readiness of female students for motherhood, and based on this research, an example of a training class program that can be used by psychologists to work with expectant mothers who have a low level of psychological readiness for motherhood is developed and presented. The authors justified the need to create new research methods of psychological readiness for motherhood.The problem of motherhood has attracted the attention of psychologists for quite some time. However, such a concept as psychological readiness for motherhood is still an unknown part of women both around the world and in our country in particular. One of the reasons for abortions is a low level of psychological readiness for motherhood or its absence as such.The problem of psychological readiness for motherhood in our country has been relevant for research before. Because motherhood is a woman’s vocation by nature, a women’s mission. And only a woman who is psychologically ready for motherhood, has a sincere desire to become a mother, has chosen a partner who is "healthy" in all senses, who wants to become a father, is a fully formed personality herself, will be able to become a good mother for her children. Also, psychological readiness for motherhood is influenced by upbringing in the parental family, because most often children copy the behavior of their parents, especially if they do not know how to do otherwise. Thus, psychological readiness for motherhood is influenced by many factors.However, with the beginning of the war in our country, unknownness, constant stress, and fear for life (your own, your partner’s, your future child’s, your family’s, and even strangers’’) were added to such general problems. Along with this, the demographic situation is significantly deteriorating, and the mission of psychologists is to support and work on the formation of the same psychological readiness for motherhood in women.So, it is necessary to create new methods of research that would correspond to the current situation in the country. Because the old methods are not adapted to our realities.
Keywords: psychological readiness for motherhood; pregnancy; motherhood; parenting style; parents; children; family